СОВРЕМЕННОЕ СОСТОЯНИЕ И ОСНОВНЫЕ НАПРАВЛЕНИЯ РЕФОРМ СИСТЕМЫ ЗДРАВООХРАНЕНИЯ В КАЗАХСТАНЕ - Орынбасарова, С Е (Journal of Economic Research & Business Administration, 2015)
This article discusses the current state of the health system in Kazakhstan. On the basis of statistical data analysis of this system.